(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Jelakcatur Village is a village located in Kalitengah District, where the district has a basin contour or what is called Bonorowo and is included in the River Basin Area (DAS), which is prone to flooding, so that every year it is always affected by flood disasters. Based on the results of discussions with partners, the problems faced related to flooding are: Low knowledge of youth in Karang Taruna regarding flood mitigation has implications for low community preparedness for flood disasters; The unavailability of physical infrastructure for handling floods, namely EWS, which is able to provide up-to-date information about flood disasters; The unavailability of flood disaster hazard maps, safe zones, and evacuation routes. The purpose of this activity is to provide solutions in the form of: increasing the knowledge of youth in Karang Taruna regarding preparedness in facing flood disasters through counseling and education about floods to Karang Taruna in order to increase understanding, concern, and the role of youth in their environment; Making an IoT-integrated EWS so that it can provide early warning information for flood disasters to the Jelakcatur Village community in real time; Making disaster hazard maps in a participatory manner, namely safe zone maps and evacuation routes, to provide the community with an understanding of environmental conditions related to flood disasters. This participatory flood disaster evacuation route map-making training activity is a supplement to increase the capacity of Karang Taruna cadres in non-structural disaster mitigation carried out at the pre-disaster stage, as well as to improve the soft skills of Karang Taruna cadres so that they can increase their role in the local village.